Pedagogical Competence of EFL Teachers: Teachers’ and Students’ Perspectives - Kadek Ngurah Kusumayasa (Universitas Pendidikan Ganesha, 2022)
The pedagogic competence of English teachers plays an important role in developing students' potential in mastering English. Students' perceptions are needed to find out how the teacher's pedagogic competence is in carrying out learning, students can be used as sources of information for reflection because students often interact directly with teachers in the learning process. In addition, the perception of the teacher itself is also needed to find out how his pedagogical competence as a teacher is in carrying out the learning process in order to achieve learning objectives. This study aims to analyze teacher and student perceptions of the pedagogical competence of English teachers and analyze differences in student and teacher perceptions related to pedagogical competence in teaching English. This research is a mixed method research. Data collection in this study used instruments in the form of questionnaires and interviews. The results showed that students' perceptions of their English teacher's pedagogic competence were categorized as positive because the average of all student responses was 4.3547. The English teacher's perception of his pedagogical competence is categorized as positive because the average of all teacher responses is 4.4222. Students and teachers have different perceptions about the teacher's pedagogic competence in teaching English, namely in terms of understanding the characteristics and potential of students.